2020
DOI: 10.1101/2020.04.27.20078329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-scale testing can suppress the spread of COVID-19

Abstract: We propose an additional intervention that would contribute to the control of the COVID-19 pandemic, offer more protection for people working in essential jobs, and help guide an eventual reopening of society. The intervention is based on: (1) testing every individual (2) repeatedly, and (3) isolation of infected individuals. We show here that at a sufficient rate of testing and isolation, the R0 of SARS-CoV-2 would be reduced well below 1.0, and the epidemic would collapse. The approach does not rely on stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
103
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 34 publications
(38 reference statements)
0
103
0
Order By: Relevance
“…100 To do so, large population screening is necessary; thus the assay must be high throughput, rapid, and cheap. 6,10,51,101,102 For example, Bendavid et al used an LIFA to test the prevalence of SARS-CoV-2 antibodies in 3330 people from Santa Clara County, California. The results indicated that 2.49% (95% CI: 1.80-3.17%) to 4.16% (95% CI: 2.58-5.70%) people in Santa Clara might be SARS-CoV-2 infected.…”
Section: Prospectivementioning
confidence: 99%
See 2 more Smart Citations
“…100 To do so, large population screening is necessary; thus the assay must be high throughput, rapid, and cheap. 6,10,51,101,102 For example, Bendavid et al used an LIFA to test the prevalence of SARS-CoV-2 antibodies in 3330 people from Santa Clara County, California. The results indicated that 2.49% (95% CI: 1.80-3.17%) to 4.16% (95% CI: 2.58-5.70%) people in Santa Clara might be SARS-CoV-2 infected.…”
Section: Prospectivementioning
confidence: 99%
“…The graph was obtained from an online interactive dashboard developed by the Center for Systems Science and Engineering (CSSE) at Johns Hopkins University, Baltimore, MD, USA 5 symptomatic. [6][7][8] Thus, the identification and isolation of infected people is paramount in fighting COVID-19 since vaccines and effective antiviral drugs have not yet been developed. 6,9 Tremendous efforts have been employed to develop highly accurate diagnostic testing for COVID-19 since January 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…he emergence of the novel human coronavirus in late 2019 in the Wuhan region of China rapidly evolved into a global pandemic. The high transmission rate and high proportion of asymptomatic infections led to a massive, worldwide need for rapid, affordable, and efficient diagnostic tests, that can be performed in clinical and non-clinical settings 1,2 .…”
mentioning
confidence: 99%
“…contact tracing and focused quarantining can significantly suppress disease spread [1][2][3] and has significantly impacted disease transmission rates, the number of infected people, and prevented saturation of the healthcare system [4][5][6][7] . However, reliable systems allowing for parallel testing of 10-100,000's of patients in larger urban environments have not yet been employed.…”
mentioning
confidence: 99%